When is entrepreneurial orientation beneficial for new product performance? The roles of ambidexterity and market turbulence. Issue 1 (21st September 2020) - Huang, Shuangfa; Pickernell, David; Battisti, Martina; Soetanto, Danny; Huang, Qihai
Abstract : Purpose: Entrepreneurial orientation (EO) is an exploratory orientation because its dimensions such as innovativeness, proactiveness and risk-taking are the essence of exploration that entails uncertain returns. While literature suggests firms might need to counterbalance and complement EO with another orientation for organisational success, research on this area remains limited. Drawing on organisational learning theory, the purpose of this article is to explore whether and how the EO dimensions and organisational ambidexterity complement each other to enhance new product performance. More specifically, the authors explore the configurations of innovativeness, proactiveness, risk-taking and ambidexterity for superior new product performance under different levels of market turbulence. Design/methodology/approach: Based on a configurational perspective, the authors applied fuzzy set qualitative comparative analysis (fsQCA) on a sample of 88 small and medium-sized firms from the UK. Using fsQCA allows the authors to uncover the potential complementary role between the EO dimensions and ambidexterity for superior new product performance. Findings: The results of this paper reveal three configurations that are sufficient to produce superior new product performance. The results suggest that the EO dimensions and ambidexterity can complement each other to enhance new product performance. Further, under the turbulent market environment, the EO dimensions are also sufficient to produce superior new product performance. Originality/value: By adopting a configurational perspective using fsQCA, the study provides a more holistic understanding of how the EO dimensions work together to influence new product performance. It also contributes to the literature by uncovering the complementary role of the EO dimensions and ambidexterity in shaping new product performance.